Structure engineering of naphthalene diimides for improved charge carrier mobility: self-assembly by hydrogen bonding, good or bad? - Kolhe, Nagesh B.; Devi, R. Nandini; Senanayak, Satyaprasad P.; Jancy, B.; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry, 2012)
Two families of naphthalene diimide (NDI) derivatives were compared and contrasted for the effect of self-assembly on charge carrier transport. One series of NDI derivatives had a terminal phenyl ring attached to a hexyl spacer substituted naphthalene core either through an ester or an amide linkage (NDI-E and NDI-A, respectively), while the other series had a 3,4,5-tridodecyloxy phenyl unit (NDI-E3, NDI-A3) instead of the terminal phenyl unit. Solution processed thin films of these molecules exhibited n-type charge transport characteristics in a bottom gate top contact organic field effect transistor (OFET) geometry. The amide derivatives showed evidence of self-organization with observation of red shifted aggregate emission in solution as well as solid state. Variable temperature FTIR studies in the solid state confirmed the existence of strong hydrogen bonding which could be broken only at very high temperature. However, contrary to expectations, the NDI ester derivatives showed better device efficiency with electron mobilities in the range 8.5 x 10(-3) to 2 x 10(-2) cm(2) V-1 s(-1) and on/off ratio similar to 10(4). The thin film crystallinity and morphology of NDI-E and NDI-A were examined through X-ray diffraction and atomic force microscopy (AFM). The correlation of crystallinity, hydrogen bonding and charge carrier mobility was studied using energy minimized structures from density functional theory (DFT). The higher electron mobility of ester linked NDI derivatives over the amide linked ones was attributed to the freedom in charge transport pathways offered by a three dimensional crystalline organization in the ester compared to the restricted directional hydrogen bonding interaction in the amide derivatives.

Selective imaging of quorum sensing receptors in bacteria using fluorescent Au nanocluster probes surface functionalized with signal molecules - Mukherji, Ruchira; Samanta, Anupam; Illathvalappil, Rajith; Chowdhury, Somak; Prabhune, Asmita; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2013)
Fluorescent ultrasmall gold clusters decorated with bacterial quorum sensing signal molecules, acyl homoserine lactone, are synthesized. These fluorescent probes are found to have emission in the near-infrared spectral region advantageous for bioimaging. Imaging studies using different. strains of bacteria with and without acyl homoserine lactone receptors with the aid of confocal microscopy have shown that the probe interacts preferentially with cells possessing these receptors. This indicates that, with appropriate surface functionalization, the Au clusters can be used for receptor specific detection with enhanced selectivity.
Keywords: Au nanoclusters; Biosensor; fluorescence imaging; quorum sensing

Surface site modulations by conjugated organic molecules to enhance visible light activity of ZnO nanostructures in photocatalytic water splitting - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Journal of Physical Chemistry C, 2015)
Surface modification of ZnO nanoparticles is identified as a method of modulating surface sites advantageously. ZnO nanoparticles of two different sizes are surface modified with a conjugated organic moiety to enable electron conduction and transfer. Enhanced H-2 evolution from water-methanol mixtures was observed in the composite systems compared to pristine ZnO under visible light irradiation without any cocatalyst. The system is also marginally active in water splitting in pure water without any sacrificial agents. Photophysical characterization indicates that even though reducing size into the nanoregime affects the band gap detrimentally, modifications by simple conjugated organic molecules assist in enhanced visible light activity. The experimental observations are corroborated with computational studies, which also point to a localization of valence band maximum of the interface on the organic moiety and conduction band minimum on ZnO.

Sensitizing with short conjugated molecules: multimodal anchoring on ZnO nanoparticles for enhanced electron transfer characteristics, stability and H-2 evolution - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Catalysis Today, 2018)
Sensitizing semiconductors with organic dyes is usually employed to improve efficiency of semiconductors towards visible light absorption and charge transport. However, till date most of the dyes are either noble metal based with complex and expensive synthesis procedure or have a very narrow absorption band. Further the photostability of the dyes is another important issue. In this work we have studied, using a combination of photophysical and computational methods, ZnO nanoparticles sensitized with transition metal free, cheap and easy to synthesize azoquinoline dye that has been designed to have multiple chelating sites, viz., carboxylic group and hydroxyl imine group as a photocatalyst for water splitting activity. We find that the presence of multiple chelating sites facilitates dual mode of anchoring on ZnO nanoparticles, which leads to enhanced photostability and H-2 generation of the composite. This is attributed to the incorporation of resonance features in the dye that increases electron transfer between ZnO and dye in contrast to the charge accumulation and photo degradation observed in non-conjugated and single site anchoring counterparts. Electron transfer from ZnO to dye under UV light and reverse in visible light could be identified experimentally. Such simple designing aspects can aid in identifying better catalysts for photocatalytic water splitting.

Synergistic effect of B site co-doping with Co and Ce in bifunctional oxygen electrocatalysis by oxygen deficient brownmillerite Ba2In2O5 - Thundiyil, Shibin; Kurungot, Sreekumar; Devi, R. Nandini (Catalysis Today, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Specificity in oxygen reduction and evolution reactions is pivotal in bifunctional catalysts in advanced energy devices which are expected to be active in a wide potential window and stable in both electrochemically reducing and oxidising atmospheres. State of the art noble metal catalysts for these reactions are fraught with issues whereas, metal oxides are expected to be stable in large potential window and can be tuned to have better bifunctional activity. Catalytically active metals, redox centres, oxygen vacancies etc. are some of the features of structured oxides which can be exploited in oxygen electrocatalysis. Brownmillerite family of compounds with general formula, A<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">B<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> has high concentrations of ordered oxygen vacancy in a layer and can be promising bifunctional oxygen electrocatalysts, by appropriate B site doping. Ba<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> is a well-studied system for its oxide ion conductivity and proximity of active B sites to O vacancies provide good O adsorption sites which are catalytically active. Here, cobalt and cerium are co-doped in Ba<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, anticipating a synergistic effect of Ce(III)/Ce(IV) redox centre in ORR and Co activity in OER along with O vacancies providing adsorption sites. We have studied the structural changes associated with the doping by Rietveld refinement of the XRD patterns and correlated the structure to bifunctional oxygen electrocatalytic activity which is found to enhance on increasing the Co and Ce content.

Scalable optical fiber reactor for photocatalytic H2 production: addressing scattering issues - Walko, Priyanka S.; Devi, R. Nandini (International Journal of Hydrogen Energy, 2023)
Scattering is one of the main challenges in scaling up photocatalytic water splitting using the most prevalent powder catalysts. This can be overcome by decoupling the reaction medium from light transmission, as in the case of optical fibers. Here we explore utilizing optical fibers coated with 5 wt% CuO supported on TiO2 for photocatlytic H2 production from water-methanol mixtures. CuO/TiO2 is a well studied photo catalyst in which photoreduced Cu species are known to act as sensitizers for inducing visible light activity. Lower activity of sequentially coated systems indicates that appropriate interfaces of active Cu and TiO2 with water are desirable. The scalability of such optical fiber-based systems along with potential in non-potable turbid water media are demonstrated. Maximum activity of 22 mmoles of H2 in 8 h was obtained with 50 mg of catalyst coated on optical fibers, which increases linearly with increase in fiber numbers, whereas, drastic reduction in activity is observed in powder catalyst upon increasing the catalyst quantity. A one-to-one comparison of 700 mg of catalyst in powder form and coated on optical fibers indicates more than one order enhancement in activity in the optical fiber based system. In addition, -70% retention in activity in highly turbid non-potable water was observed as compared to powdered system which shows complete reduction in the activity by 99.99%. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CuO; Optical fibers; photocatalytic water splitting; TiO2; Total internal reflection; Visible light utilisation